Combination of Ozonation and Adsorption Using Granular Activated Carbon (GAC) for Tofu Industry Wastewater Treatment - Eva Fathul Karamah; Ika Putri Adripratiwi; Linggar Anindita (Universitas Gadjah Mada, 2018)
Tofu industry wastewater is one of the environmental pollutants that need more effective treatment. Ozonation and adsorption method is known to have the capability to oxidize organic compound in wastewater. Adsorption is done by using granular activated carbon (GAC) as an adsorbent to increase tofu wastewater degradation process by adsorbing organic materials and increasing production of hydroxyl radical as the main oxidizing agent. This research is carried out to evaluate the performance of ozonation, adsorption, and combination of both in processing tofu wastewater. To evaluate the significance of ozone dosage and amount of GAC used, these variations are varied which are 60, 111, and 155 mg/h of ozone dosage and 50, 75, and 100 g of the amount of GAC used. Parameters of the process are organic substances of tofu wastewater such as COD, TSS, and pH. The measurements are being done using a spectrophotometer, colorimeter, and pH meter. The outcome of this research is to provide an alternative method in the liquid waste treatment of the tofu industry and the processed wastewater to meet the environmental quality standards. The more ozone and the more quantity of GAC used, the higher the quantity of hydroxyl radicals formed. Addition of GAC in the ozonation process results in more than 100% increase in hydroxyl radical production. Combination of ozonation and adsorption is able to remove 377.12 mg/L of COD and 26 mg/L of TSS.